2022
DOI: 10.4103/0972-9062.342400
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Crimean-Congo Haemorrhagic Fever (CCHF) virus in hard ticks from South Khorasan, east of Iran

Abstract: Background & objectives: Crimean-Congo Hemorrhagic Fever (CCHF) is a deadly viral infection reported from more than 30 countries. It is considered a zoonosis↱ and tick bites are the main route of transmission in nature. So far, the virus has been identified in 31 species of hard (Ixodidae) and soft (Argasidae) ticks. The aim of this study was to determine the rate of CCHF virus infection in hard ticks from South-Khorasan province, east of Iran. Methods: In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…These strains exhibited strong genetic similarities with those reported from neighboring countries such as Iran, Afghanistan, India, and Oman, indicating a close link in transmission among these regions. It has been suggested that the frequent trade of animals might facilitate the movement of the virus between Pakistan and its neighboring countries [7,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…These strains exhibited strong genetic similarities with those reported from neighboring countries such as Iran, Afghanistan, India, and Oman, indicating a close link in transmission among these regions. It has been suggested that the frequent trade of animals might facilitate the movement of the virus between Pakistan and its neighboring countries [7,[25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Ticks that tested positive belonged to the Hyalomma and Rhipicephalus genera. All infected ticks were recovered from goats and sheep in Birjand [101].…”
Section: Standard Reverse-transcriptase Pcr (Rt-pcr)mentioning
confidence: 99%
“…It is known that any deformation in blood cells can cause highly serious disturbance in their functions 11 . At least 31 different tick species can transmit CCHFV 12 . Hyalomma species' wide distribution which includes different types of environments such as dessert can relate to their capacity to adapt and manage their survival in thus environments 13 .…”
Section: Introductionmentioning
confidence: 99%